The Impact of Slow Stroke Back Massage on Blood Pressure and Pulse in Hypertensive Patients Aged 45–54 Years - Yusamto, Intan Clarisa Yuli; Sepdianto, Tri Cahyo; Mujito, Mujito (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Hypertension is a non-communicable disease that kills silently. The aim of this research is to determine the effect of slow stroke back massage on blood pressure and pulse in hypertension sufferers aged 45-54 years in Blitar City. This research uses a quantitative type of research with a pre-experimental research design with a One-Group Pretest-Posttest design approach. The samples taken were hypertension sufferers aged 45-54 years who underwent examinations at the Blitar City Health Center UPTD with a sample size of 30 respondents, and sampling used purposive sampling. This research instrument uses a digital sphygmomanometer and oximetry. SSBM is carried out for 15 minutes with 2 massages for 2 weeks which aims to reduce blood pressure and pulse in hypertension sufferers. The data was processed descriptively and continued with the Paired t Test. The results show that the average systolic pressure before is 154.70, the average diastole before is 90.23, the average pulse before is 86.67, and the average systolic pressure after is 152.13, the average diastole after is 88.23, the average pulse after is 84.03. The results of statistical tests using the Paired t Test show a value of P=0.000 (p<0.05), so there is a significant difference in the blood pressure and pulse values before and after. The results of the research show that there is a decreasing effect on blood pressure and pulse before and after being given Slow Stroke Back Massage therapy and can be used as a non-pharmacological therapy at the Blitar City Health Center UPTD for hypertension sufferers.